RICE PRODUCTION INPUT ANALYSIS IN ASAHAN DISTRICT - Hazlansyah - Ramelan (Universitas Negeri Medan, 2022)
This study aims to determine the effect of land area, labor, fertilizer and pesticides on the production of lowland rice in Asahan Regency. This study uses secondary data obtained from the Central Statistics Agency (CSA) of the Ministry of Agriculture, the Department of Trade, the Department of Agriculture of Food Crops District and North Sumatra Province and other institutions related to the object of research. The tool used to process the data is the Eviews 8.0 program. Data analysis techniques in this study used the OLS (Ordinary Least Square) method, classical assumption test and statistical test. The results showed that: 1) land area had a significant effect and had a positive coefficient on rice production; 2) labor does not have a significant effect and has a negative coefficient on rice production; 3) fertilizer is not significant and has a positive coefficient on rice production; 4) pesticides have a significant effect and have a positive coefficient on rice production.___________________________________________________________________Keywords : Land Area, Labor, Fertilizer Prices, Pesticide Prices and Rice Production